1994
DOI: 10.1073/pnas.91.25.12110
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of ELL, a gene that fuses to MLL in a t(11;19)(q23;p13.1) in acute myeloid leukemia.

Abstract: To characterize the functions of MLL fusion transcripts, we cloned the gene that fuses to MLL in the translocation t(11;19)(q23;p13

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
176
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 26 publications
(23 reference statements)
3
176
0
Order By: Relevance
“…A sequence homology search revealed that the D40 sequence is the same as that of the AF15q14 gene (Hayette et al, 2000). This gene is a partner that fuses with MLL, an oncogenic gene involved in the development of acute leukaemia (Hunger et al, 1993;Thirman et al, 1994;Hernandez et al, 1995;Dimartino and Cleary, 1999). In contrast to normal tissues, D40 was expressed in all human cancer cell lines examined and in several primary human tumours independently of the types and source of the tumours.…”
Section: Discussionmentioning
confidence: 99%
“…A sequence homology search revealed that the D40 sequence is the same as that of the AF15q14 gene (Hayette et al, 2000). This gene is a partner that fuses with MLL, an oncogenic gene involved in the development of acute leukaemia (Hunger et al, 1993;Thirman et al, 1994;Hernandez et al, 1995;Dimartino and Cleary, 1999). In contrast to normal tissues, D40 was expressed in all human cancer cell lines examined and in several primary human tumours independently of the types and source of the tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Many lines of evidences demonstrate that truncations of MLL are restricted within a 0.9 kb fragment in cDNA and a 8.5 kb fragment in genome DNA in humans (Bernard et al, 1994;Chaplin et al, 1995;Corral et al, 1993;Iida et al, 1993;Mitani et al, 1995;Prasad et al, 1993;Thirman et al, 1993Thirman et al, , 1994Trent et al, 1989;Tse et al, 1995;Yamamoto et al, 1993b). Ten translocation partner genes fused to MLL have been cloned to date, but no common structure has been found (Bernard et al, 1994;Corral et al, 1993;Mitani et al, 1995;Nakamura et al, 1993;Tkachuk et al, 1992;Tse et al, 1995), suggesting that the N-terminal portion of MLL plays an important part in leukemogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In leukemias with 11q23 translocations, MLL is disrupted and the N-terminal portion, including the AThook motifs and the DNA methyltransferase homology region, is fused to various translocation partner genes, such as AF4/FEL, LTG9/AF9 and LTG19/ENL (Gu et al, 1992;Iida et al, 1993;Morrissey et al, 1993;Nakamura et al, 1993;Tkachuk et al, 1992;Yamamoto et al, 1993a,b). Although more than ten di erent chromosomal translocation partner genes have been identi®ed (Thirman et al, 1993;Trent et al, 1989), no shared common structure has been recognized among the partner gene products (Bernard et al, 1994;Chaplin et al, 1995;Corral et al, 1993;Iida et al, 1993;Mitani et al, 1995;Nakamura et al, 1993;Prasad et al, 1993;Thirman et al, 1994;Tse et al, 1995;Yamamoto et al, 1993b). We previously demonstrated that the chimeric MLL products MLL-LTG9 and MLL-LTG19, as well as MLL-Zf (7), the N-terminal portion common to various chimeric MLL products, localize in nuclei (Joh et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…U19/Eaf2 shows significant sequence homology to the original family member, Eaf1. ELL was discovered as a fusion partner of MLL in the t(11; 19) (q23; p13.1) chromosomal translocation associated with acute myeloid leukemia (Thirman et al, 1994). ELL binds to RNA polymerase II and acts as a transcription elongation factor whose targeted deletion leads to embryonic lethality in mice (Shilatifard et al, 1996(Shilatifard et al, , 1997aMitani et al, 2000).…”
Section: Introductionmentioning
confidence: 99%